Normative Evaluation of Presidential Powers in Emergency Situations: Constitutional Limits and Legal Guarantees in Indonesia - Furqon, Wahyul; Djuhrijjani, Djuhrijjani (IJBLE Scientific Publications Community Inc., 2025)
This study examines the exercise of presidential powers in emergency situations within the framework of Indonesia’s 1945 Constitution, focusing on constitutional limits and legal guarantees. Using a qualitative approach with a normative juridical methodology, the research analyzes constitutional provisions, statutory regulations, and judicial practices to evaluate the effectiveness of Indonesia's legal framework in balancing crisis management with the preservation of democratic principles. The findings reveal ambiguities in emergency criteria, gaps in accountability mechanisms, and concerns over proportionality in restricting fundamental rights. Comparative insights and recommendations are provided to enhance legal clarity, strengthen oversight, and safeguard constitutional democracy during emergencies.